2017
DOI: 10.4172/2168-9784.1000258
|View full text |Cite
|
Sign up to set email alerts
|

Proficiency Test Feedback Utilization at Government Hospitals Laboratory, Addis Ababa, Ethiopia

Abstract: Background: Proficiency testing (PT) is the most commonly employed type of External Quality Assurance (EQA) and a tool to measure laboratory performance. Participating in PT is crucial for clinical laboratories that will help the participating laboratory to reduce errors, produce accurate patient test results and most importantly improve patient care by taking corrective action accordingly. The aim of this study is to assess the utilization of PT result in their laboratory Service and Identify challenges relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 15 publications
0
4
1
Order By: Relevance
“…This might be due to low participation, PT samples not being performed because of reagent unavailability and/or equipment failure, not using appropriate units of measurement for the PT result report, or a lack of corrective actions taken for PT nonconformances. However, these findings are lower than those of a study conducted in Addis Ababa, Ethiopia 18 , in which the failure rate was 63.2%. The variations in the number of study years and laboratory test parameters included in this study might be possible reasons for the differences.…”
Section: Discussioncontrasting
confidence: 78%
“…This might be due to low participation, PT samples not being performed because of reagent unavailability and/or equipment failure, not using appropriate units of measurement for the PT result report, or a lack of corrective actions taken for PT nonconformances. However, these findings are lower than those of a study conducted in Addis Ababa, Ethiopia 18 , in which the failure rate was 63.2%. The variations in the number of study years and laboratory test parameters included in this study might be possible reasons for the differences.…”
Section: Discussioncontrasting
confidence: 78%
“…In this study the average PT performance the 6 PT events for 28 PT programs was 67.75% success rate even though significant improvement is not observed through the trend of PT event which among participated facilities those graded as ACC or UNACC which account 97507 (79.9%) among the total PT challenges distributed and the success rate or the rate of scoring ACC were 66.00%, 67.61%, 67.22%, 67.35%, 67.48% and 70.87% which showed relatively good performance compared to the study conducted among 12 government hospitals laboratories in Addis Ababa, who had been participated in proficiency tasting schemes for 20 clinical laboratories test parameters in 6 cycles from 2012 to 2013 G. C. in over 6 cycle showed that those meet the analytical performance score of 80 and above is 40.42%, 26.67%, 26.67%, 51.67%, 37.09%, 38.37% this indicates no improvement in quality through time [9]. This study was comparable with the study conducted in Nigeria between 2009 and 2011 [7].…”
Section: Performance Ratementioning
confidence: 83%
“…This is because of outdated infrastructure, poor development and application of quality management systems, and insufficient involvement in EQA programs. 27 Participation in the EQA program in resource-limited countries faced different challenges, including sample commutability and assigned target values; transportation and shipment; expenses from the EQA program; equipment and reagent supplies; awareness and motivation of laboratory professionals; and utilization of feedback, which has a direct impact on the implementation of the EQA.…”
Section: Challenges To External Quality Assessmentmentioning
confidence: 99%
“… 11 However, the major challenge for the implementation of an EQA program is that most employees lack knowledge and expertise, and they do not fully understand the objective of PT, which leads to a failure to identify gaps based on EQA feedback. 15 , 27 …”
Section: Staff Awareness and Motivationmentioning
confidence: 99%
See 1 more Smart Citation